1989
DOI: 10.1007/bf01270432
|View full text |Cite
|
Sign up to set email alerts
|

Control of induced infestations of three African multihost tick species with sustained-release ivermectin

Abstract: The efficacy of ivermectin, released intraruminally from a 28-day-delivery device was evaluated in two titration studies against induced infestations of adult Rhipicephalus appendiculatus, R. evertsi and Hyalomma truncatum on cattle. Cattle were given a sufficient number of devices to release ivermectin at approximately 20, 40, 60 or 80 micrograms kg-1 day-1 at a steady-state rate 7-28 days after administration. Tick mortality was recorded, engorged female ticks were weighed and individually incubated, and rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

1989
1989
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…However, the current unavailability of the bolus does not diminish its potential for long-term toxic impact in cow-pats. It is significant that the same devices, some delivering 50% more ivermectin than that examined by Wall & Strong (1987), are constantly being tested against arthropod and nematode pests of cattle (Soil et a\., 1989;Taylor & Kenny, 1990;Zimmerman et ah, 1991); no one can doubt that it is only a matter of time before the bolus is marketed. The consequences for dung insects and pastureland ecology will be severe (Wall & Strong, 1987;), a conclusion supported by Houlding et al (1991) who assert that the detrimental impact of abamectin on Australian dung beetles could be considerably more serious if sustained-release administration were to be deployed.…”
Section: Impact Of the Type Of Treatmentmentioning
confidence: 97%
“…However, the current unavailability of the bolus does not diminish its potential for long-term toxic impact in cow-pats. It is significant that the same devices, some delivering 50% more ivermectin than that examined by Wall & Strong (1987), are constantly being tested against arthropod and nematode pests of cattle (Soil et a\., 1989;Taylor & Kenny, 1990;Zimmerman et ah, 1991); no one can doubt that it is only a matter of time before the bolus is marketed. The consequences for dung insects and pastureland ecology will be severe (Wall & Strong, 1987;), a conclusion supported by Houlding et al (1991) who assert that the detrimental impact of abamectin on Australian dung beetles could be considerably more serious if sustained-release administration were to be deployed.…”
Section: Impact Of the Type Of Treatmentmentioning
confidence: 97%
“…The effects of ivermectin on ixodid ticks are not only of chemotherapeutic importance but also have inherent biological interest. A diverse number of sublethal effects have been recorded amongst ticks feeding on livestock treated with ivermectin, including the inhibition of engorgement, premature detachment, and reduced fecundity (Drummond et al, 1981;Lancaster et al, 1982;Soll et al, 1987) suggesting that GABA may play a central role in neurotransmission. This view is reinforced by in-vitro experiments which have demonstrated that ivermectin inhibits neurotransmission within both isolated tick neuromuscular junctions and salivary gland tissue (Gration et al, 1986;Kaufman et al, 1986;Lindsay and Kaufman, 1986); the latter plays a central role in the co-ordination of the processes of feeding, detachment and vitellogenesis in ticks.…”
Section: Introductionmentioning
confidence: 98%
“…Numerous studies have shown that ivermectin can control a variety of tick species (Drummond et al 1981. Nolan et al 1981Lancaster et al 1982;Miller et al 1983Miller et al , 1998Pegram and Lemche 1985;Cramer et al 1988;Taylor and Kenny 1990, Soll et al 1989.…”
Section: Because Of the United States Boophilus Eradicationmentioning
confidence: 98%